PENYULUHAN PEMBUATAN TEH KUNYIT (Curcuma Domestica) DI DUSUN PESULINGAN KECEMATAN TAMAN RAJO KABUPATEN MUARO JAMBI - Rasmala Dewi; Jumatul Chairiyah; Chairun Nisa; Ryan Afandi; Anggelia Pratiwi (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2020)
Guideance on making turmeric tea (curcuma domistica) by adding honey. Herbal tea are usually made from turmeric rhizome brewed with hot water. Teabag is a tea wrapped in clip paper. Processing of herbal turmeric tea that is with sorting raws maerials, the drying is done by using sundirectly to dry, raw material in chopped, and material packing. Turmeric rhizome pants are often used a amixture in cooking by the public. The contained compound on turmeric is atsiri, resin, curcumin, oleoresin, desmotoksikurkumin, grease, calcium, proyein and posfor and iron. The curcumin its benefits as an antioxidant, antimicrobe, antifunction, antifungal, and also antiinfamation. Besides curcumin is also believed to be able to inhibit growth cancer cell and meantmacu apoptosisi cancer cell.